2009
DOI: 10.1590/s1517-86922009000200008
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos fisiológicos agudos da taurina contida em uma bebida energética em indivíduos fisicamente ativos

Abstract: Segundo a Secretaria de Vigilância Sanitária do Ministério da Saúde, bebidas energéticas são identificadas como compostos líquidos prontos para o consumo, sendo estas constituídas de carboidratos, taurina, cafeína, glucoronolactona, inositol e vitaminas do complexo B. Existem poucas pesquisas sobre o uso de taurina contida em bebidas energéticas relacionado com a melhora de desempenho. Este trabalho teve como objetivo analisar as respostas metabólicas e hemodinâmicas decorrentes da administração da associação … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Candow et al [78] did not find any differences between an energy drink and placebo among 17 university students after performing a time-to-exhaustion treadmill run at 80% VO 2 max (Red Bull ® : 12.6 ± 3.8 min, placebo: 11.8 ± 3.4 min; perceived exertion Red Bull ® : 17.1 ± 2.0, placebo: 16.6 ± 1.8). Nor did Dall'Agnol and Souza [79] report any differences during an incremental exercise test performed in 22 healthy volunteers after they ingested either 160 mg of caffeine with 2000 mg of taurine or placebo (332.50 ± 56.83 vs. 342 ± 40.60 W), while Kammerer et al [80] did not find any differences in VO 2 max values after volunteer soldiers consumed an energy drink compared to a placebo-controlled scenario. In the same vein, Pettitt et al [81] observed that consuming an energy drink did not improve the gas exchange threshold in eight recreationally trained subjects during a graded exercise test on a cycle ergometer.…”
Section: Energy Drinks Combining Caffeine and Taurine In Sport Performentioning
confidence: 92%
“…Candow et al [78] did not find any differences between an energy drink and placebo among 17 university students after performing a time-to-exhaustion treadmill run at 80% VO 2 max (Red Bull ® : 12.6 ± 3.8 min, placebo: 11.8 ± 3.4 min; perceived exertion Red Bull ® : 17.1 ± 2.0, placebo: 16.6 ± 1.8). Nor did Dall'Agnol and Souza [79] report any differences during an incremental exercise test performed in 22 healthy volunteers after they ingested either 160 mg of caffeine with 2000 mg of taurine or placebo (332.50 ± 56.83 vs. 342 ± 40.60 W), while Kammerer et al [80] did not find any differences in VO 2 max values after volunteer soldiers consumed an energy drink compared to a placebo-controlled scenario. In the same vein, Pettitt et al [81] observed that consuming an energy drink did not improve the gas exchange threshold in eight recreationally trained subjects during a graded exercise test on a cycle ergometer.…”
Section: Energy Drinks Combining Caffeine and Taurine In Sport Performentioning
confidence: 92%